Analysis of 5C principles in measuring the credit quality of two-wheeled vehicle consumers at PT. Mandala Multifinance, Tbk Makassar Branch 3 - Daniel Deky Bakker; Syamsu Alam; Erlina Pakki (Hasanuddin Journal of Applied Business and Entrepreneurship, 2022)
This study aims to determine the effect of the 5C principle on the credit quality of two-wheeled vehicle consumers at PT. Mandala Multifinance, Tbk Makassar Branch 3. This research is a quantitative study using multiple regression analysis with the help of the SPSS application. Data were collected through the distribution of questionnaires to 138 consumers. Test the validity and reliability of the questionnaire conducted before distributing it to the intended respondents. Based on the results of the study, the character variable has a negative effect on credit quality, the capacity variable has a negative effect on credit quality, the capital variable has a positive effect on credit quality, the guarantee variable has a negative effect on credit quality, the economic condition variable has a negative effect on credit quality for two-wheeled vehicle consumers in Indonesia. PT. Mandala Multifinance, Tbk Makassar Branch 3.